Pharmacognostical and phytochemical analysis of different parts of Bryonia laciniosa L. - SHASHIKALA M,; MAMATA SHAH, (International Journal of Pharma and Bio Sciences, 2018)
Bryonia laciniosa L. is one of the common herbs used in ayurvedic and homoeopathic medicine. The present study on macroscopy and microscopy of Bryonia laciniosa L. reveals the peculiar characteristic of the plant. The leaves are palmate and seeds have characteristic Shivlingi-like shape. Microscopical study shows the presence of the two rings of vascular bundle in the stem, dorsiventral leaf with two palisade layers below the upper epidermis, roughly 5-6 angled epidermis in petiole. The T.S. of seed is divided into outer and inner integuments. The cells of the mesocarp of the fruit are filled with abundant starch and show small curved vascular strands. The root shows the presence of characteristic triangular shaped vascular bundles. The Phytochemical screening of extracts of different parts of the plant showed the presence of alkaloids, glycosides, phytosterols, tannins, phenols, saponins, flavonoids, fixed oil and fats. This study would provide useful preliminary parameters for the standardization and further phytochemical investigation of the Bryonia laciniosa L.